ELABORATION AND STRUCTURAL CHARACTERIZATION OF A COMPOSITE MATERIAL BASED ON CERAMIC / POLYMER - KRIBAA, O. K.; BOUTARFAIA, A. (Courrier du Savoir; Vol. 23 (2017): COURRIER DU SAVOIR (JUIN), 2017)
The polycrystalline samples of « Ba (ZrxTi1-x)O3 » ,x = 0.50, were prepared by high temperature solid state reaction technique. The formations of the compounds were confirmed by X-Ray diffraction (XRD) analysis. Fourier transform infrared spectroscopy (FTIR) analysis confirms the formation of perovskite structure. The polymer/ceramic composites were prepared using polyvinyle chloride (PVC) as polymer matrix and Ba (ZrxTi1-x)O3 noted (BZT) as ceramics powder In a weight percentage 50/50 . We present the various preparation steps of the synthesis reaction, then we will detail the different analysis techniques applied to this material, we start first by the x-ray diffraction, thermal analysis, following FTIR spectroscopy. These studies are carried out under air atmospheric conditions help us to accumulate as much information on these materials.